Oxford English for Information Technology. Teachers Guide - Glendinning, Eric H., McEwan, John. (Oxford Oxford University Press, 2006)
Oxford English for Information Technology is a course for students of information technology and computing, or for people already working in the IT sector. It is suitable for use in universities, technical schools and on adult education programmes, with students at intermediate to advanced level who want to improve and extend their language skills in the context of IT.
Keywords: English Practice